Developmental Assignments : Creating Learning Experiences without Changing Jobs (Dutch) - McCauley, Cynthia (Center for Creative Leadership, 2008)
This book is modeled after "Eighty-Eight Assignments for Development in Place," one of the Center for Creative Leadership's most popular publications. In the years since that report was published, we have learned more about development in place--from research, from working with managers and organizations that are making use of developmental assignments, and from our colleagues in the field. We believe it is time once again to consolidate our knowledge into one tool to help leaders add developmental assignments to their own jobs and help others do the same. The tables inside this book are full of assignments. You'll also find cross-references to CCL's assessment tools: 360 by Design, Executive Dimensions, Benchmarks, Prospector, and Skillscope. If you want to target the development of specific competencies as a result of receiving feedback from any of these, the cross-references will direct you to appropriate assignments